2019
DOI: 10.3389/fpsyg.2019.00952
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Model of Personality Disorders (DSM-5) Predicts Dropout in Inpatient Psychotherapy for Patients With Personality Disorder

Abstract: Objective Criterion A serves as the fundamental diagnostic criterion of the Alternative Model of Personality Disorders in section III of the Diagnostic and Statistical Manual 5. Consisting of a self- and an interpersonal dimension, it defines the construct of personality functioning as a general and dimensional factor of personality disorders. This study aimed to explore criterion A along with well-established treatment dropout predictors, e.g., sociodemographic factors, personality disorder diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 44 publications
(50 reference statements)
1
26
0
Order By: Relevance
“…The convergent validity of the LPFS as an expert rating has been demonstrated to be substantial with regard to the presence and/or number of section II PDs [34,[42][43][44]46], the number of PD symptoms [34,40,41], psychodynamic conceptualizations of PD severity [43,44,133], as well as selfreported PD severity [34,50,138], maladaptive traits [46], and symptom distress [34,41]. In addition, studies have established associations with psychosocial functioning, short-term risk, proposed treatment intensity, and estimated prognosis [40], lifetime mental health treatment, history of substance use, mental and physical health, and social and relationship adjustment [46], as well as risk for dropout from inpatient treatment [139].…”
Section: Convergent Validitymentioning
confidence: 99%
“…The convergent validity of the LPFS as an expert rating has been demonstrated to be substantial with regard to the presence and/or number of section II PDs [34,[42][43][44]46], the number of PD symptoms [34,40,41], psychodynamic conceptualizations of PD severity [43,44,133], as well as selfreported PD severity [34,50,138], maladaptive traits [46], and symptom distress [34,41]. In addition, studies have established associations with psychosocial functioning, short-term risk, proposed treatment intensity, and estimated prognosis [40], lifetime mental health treatment, history of substance use, mental and physical health, and social and relationship adjustment [46], as well as risk for dropout from inpatient treatment [139].…”
Section: Convergent Validitymentioning
confidence: 99%
“…In another study, impairments specific to antisocial PD added incremental validity over the corresponding DSM-IV category in predicting psychopathy [56]. Elsewhere, personality functioning (especially self functioning) was a better predictor for dropout in psychotherapy for PDs than the DSM-IV categories [58]. These findings illustrate that the concept of personality functioning is beginning to empirically prove its expected added value over the current categorical classification of PDs.…”
Section: Personality Functioningmentioning
confidence: 94%
“…The treatment was a structured, disorder‐specific treatment (DST) based on evidence‐based approaches (Busmann et al, 2019; Sollberger et al, 2015). The treatment duration was 80 days followed by 10 days of partial hospitalization.…”
Section: Methodsmentioning
confidence: 99%
“…Spinhoven et al (2007) have shown that a positive alliance was associated with symptom improvement. Moreover, there is evidence that a poor therapeutic alliance predicts premature psychotherapy termination (Busmann et al, 2019; Spinhoven et al, 2007).…”
Section: Introductionmentioning
confidence: 99%